Human Subject Barrier Scale (HSBS): A Tool to Illuminate Potential Barriers in Behavioral Research. - Bishop, John; Driber-Hassall, Ellen (International Journal of Health, Wellness & Society, 2026)
This research investigation sought to discover the existence of ready-made scales to assist in determining a "first-look" level of suitability for possible participant inclusion in human subject research, but none were located. The researchers, following the advice of journal article authors and predecessors who were in similar circumstances, decided to undertake the task of constructing the required tool. The Human Subject Barrier Scale used the seven components (Awareness, Desire (to engage), Willingness (to Participate), Commitment, Knowledge, Ability, and Epiphany) of the researchers' Engaged Aging Concept as potential barriers to participation in behavioral research, as well as to assist in determining whether any of these seven barriers may prevent successful participation in human subject research. Based upon their expertise as gerontology researchers, they chose to incorporate mixed methods research into the study framework. Further, the researchers sought to use a multi-national participant base to mirror the projected participant pool. Finally, the researchers conducted a mini-peer-review of both the quantitative and qualitative research methods that were used while constructing the new scale.